C / C-SiC composite material and preparation method thereof
By connecting graphene oxide and weaving three-dimensional standards of homosexual asphalt carbon fiber prefabricated in C/C-SIC composite materials, the problem of destruction and free silicon residue of carbon fiber surface structure is solved, and the near zero expansion and excellent composite materials are realized. Mechanical performance meets the application needs of optical machine structural parts in low temperature environment.
Patent Information
- Application Number
- CN202411515506.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-10
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-29
AI Technical Summary
During the reaction seepage process of existing C/C-SiC composite materials, the surface structure of the carbon fiber is damaged, the mechanical properties are degraded, and the diffusion depth of silicon in solid-state pyrolytic carbon is limited, resulting in the residue of free silicon and damage to the material properties.
By forming a transitional layer of gallery oxide on the surface of asphalt carbon fiber surface, the carbon fiber is protected from high temperature erosion of silicon, and the woven structure and gradient multi -pore C/C composite material skeleton of the same -sex asphalt carbon fiber prefabrication of the same three -dimensional quota are limited to carbonizing carbonization The expansion of silicon and silicon achieves near zero expansion of composite materials.
It significantly improves the infiltration of carbon fiber and resin, improves the combination of interface, protects the performance of carbon fiber, and improves the density and mechanical properties of composite materials by reducing the free silicon content. Application requirements.
Smart Images

Figure BDA0005106582040000071 
Figure BDA0005106582040000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of structural and functional integrated composite materials, and in particular relates to a C / C-SiC composite material and a preparation method thereof. Background Art
[0002] Pitch carbon fiber reinforced carbon-silicon carbide composite materials (C / C-SiC composite materials) integrate the excellent mechanical and thermal properties of carbon fiber and the excellent chemical and thermal stability of silicon carbide ceramic matrix. They have excellent properties such as low density, high specific strength, low thermal expansion coefficient, high thermal conductivity, and good resistance to space radiation. They can well meet the application requirements of space optomechanical structural parts. Therefore, they have become the ideal material for the new generation of space optomechanical structural parts and one of the important development directions. They are the fourth generation of ideal optical mechanical component materials after glass, metal, and SiC ceramic materials.
[0003] Near-zero expansion C / C-SiC composite is a multi-material system consisting of pitch-based carbon fiber, pyrolytic carbon transition layer and silicon carbide ceramic layer. The intermediate phase pitch-based carbon fiber and pyrolytic carbon have the characteristic of negative thermal expansion coefficient along the fiber axis, which can limit the expansion of silicon carbide ceramic phase. By regulating the fiber volume fraction and pyrolytic carbon structure and designing the braid structure, near-zero expansion C / C-SiC composite can be obtained in theory. Unlike traditional C / C-SiC composites, the preparation of near-zero expansion C / C-SiC composites requires special structural design and preparation process to achieve near-zero thermal expansion coefficient in the plane and thickness direction of the composite.
[0004] Commonly, reactive infiltration is an important method for preparing C / C-SiC composite materials. This method has the advantages of short process flow, low manufacturing cost, and high density. It is the preferred method for high-temperature structural materials such as automobiles, high-speed rail trains, and aerospace. Reactive infiltration uses the capillary effect to infiltrate molten silicon into the pores in the carbon / ceramic composite material, and reacts with the carbon in the carbon / ceramic composite material at high temperature to generate silicon carbide to achieve ceramicization. However, during the reactive infiltration process, the interface between the carbon fiber and the pyrolytic carbon can become a channel for the infiltration of molten silicon. The infiltrated silicon reacts with the carbon fiber, destroying the surface structure of the carbon fiber and seriously damaging the mechanical properties of the carbon fiber. In addition, due to the diffusion depth of silicon in solid pyrolytic carbon, silicon carbide is only generated on the surface of pyrolytic carbon, resulting in part of the silicon infiltrated into the pores of the composite material having no carbon source to react, and remaining in the composite material in the form of free silicon, which damages the mechanical and physical properties of the composite material. Summary of the invention
[0005] The present invention aims to overcome the deficiencies of the prior art and aims to provide a near-zero expansion C / C-SiC composite material and a preparation method thereof. The technical solution of the present invention to solve the above technical problems is as follows:
[0006] A method for preparing a C / C-SiC composite material comprises the following steps:
[0007] S1 grafted graphene oxide onto the surface of asphalt carbon fiber;
[0008] S2 weaves the pitch carbon fiber obtained in S1 into a three-dimensional quasi-isotropic pitch carbon fiber preform;
[0009] S3 mixes the thermosetting resin, the curing agent and the organic solvent evenly to obtain a resin slurry, and then vacuum impregnates the asphalt carbon fiber preform obtained in S2 into the resin slurry, and then cures and cracks the asphalt carbon fiber preform until the density of the asphalt carbon fiber preform reaches 1.30-1.50g / cm 3 , a porous C / C composite skeleton is prepared;
[0010] S4: reacting and infiltrating silicon into the gradient porous C / C composite material skeleton obtained in S3 to obtain the C / C-SiC composite material; the carbon fibers in the asphalt carbon fiber preform are perpendicular to each other in three directions to form an orthogonal structure, and the edges of the asphalt carbon fiber preform form an interlocking structure;
[0011] In the X direction of the pitch carbon fiber preform, the volume fraction of the pitch carbon fiber is 15-20 vol%;
[0012] In the Y direction of the pitch carbon fiber preform, the volume fraction of the pitch carbon fiber is 15-20 vol%;
[0013] In the Z direction of the pitch carbon fiber preform, the volume fraction of the pitch carbon fiber is 8-12 vol%;
[0014] The C / C-SiC composite material has a thermal expansion coefficient of about 0.03-0.46 ppm / K in the plane direction and a thermal expansion coefficient of about 0.18-0.69 ppm / K in the thickness direction.
[0015] The S1 is to use plasma to modify the surface of the asphalt carbon fiber, and then use a silane coupling agent grafting method to graft graphene oxide on the surface of the carbon fiber.
[0016] The ions used in the plasma treatment method are one or more of Ar, N2, and O2;
[0017] The discharge power used in the plasma treatment method is 200W-800W;
[0018] The plasma treatment method uses a treatment time of 10s-100s.
[0019] The S1 comprises the steps of mixing an alcohol dispersion of graphene oxide and an alcohol solution of a silane coupling agent to obtain a coupling agent-modified graphene oxide dispersion, and then immersing the plasma-treated pitch carbon fiber in the coupling agent-modified graphene oxide dispersion, and then taking out and drying.
[0020] In the alcohol dispersion of graphene oxide, the ratio of alcohol solvent to graphene oxide is 10 mL: 30-60 mg;
[0021] In the alcohol solution of the silane coupling agent, the mass fraction of the silane coupling agent is 2-5%;
[0022] In the coupling agent-modified graphene oxide dispersion, the volume ratio of the graphene oxide alcohol dispersion to the silane coupling agent alcohol solution is 10:1-5.
[0023] The silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane and N-β (aminoethyl)-γ-aminopropyltriethoxysilane.
[0024] The method comprises vacuum impregnating the asphalt carbon fiber preform obtained in S2 in resin slurries A, B and C with increasing amounts of residual carbon, followed by curing and cracking until the density of the asphalt carbon fiber preform reaches 1.30-1.50 g / cm 3 , the step of preparing a gradient porous C / C composite skeleton;
[0025] The resin slurry A includes a thermosetting resin A;
[0026] The resin slurry B includes a thermosetting resin B;
[0027] The resin slurry C includes a thermosetting resin C;
[0028] The thermosetting resin A includes any one of epoxy resin, furan resin and trisphenol type phthalonitrile resin;
[0029] The thermosetting resin B includes any one of acetylene polyimide resin, bismaleimide resin and trisphenol type phthalonitrile resin;
[0030] The thermosetting resin C includes any one of a polybenzoxazine resin, a styrene-based polybenzoxazine resin and a phenolic resin;
[0031] The curing agent includes tetrahydrophthalic anhydride, xylene sulfonic acid, diethylenetriamine or hexamethylenetetramine;
[0032] The organic solvent includes ethanol, dimethylformamide, acetone or xylene;
[0033] In the resin slurry, the mass ratio of the thermosetting resin, the curing agent and the organic solvent is 60-120:5-10:80-140.
[0034] The vacuum degree of the vacuum impregnation is -0.1-0MPa, and the time is 1-2h;
[0035] The curing temperature is 100-150°C and the curing time is 4-16h;
[0036] The cracking temperature is 800-1200° C. and the time is 1-5 hours.
[0037] The vacuum degree of the reactive silicon infiltration is ≤1000Pa;
[0038] The heating rate of the reactive infiltration silicon is 5-10°C / min;
[0039] The insulation temperature of the reactive infiltration silicon is 1500-1800°C;
[0040] The holding time of the reactive silicon infiltration is 120-180 minutes;
[0041] The particle size of the silicon powder used for the reactive infiltration of silicon carbide is 30-50 μm, and the mass fraction of silicon in the silicon powder is ≥98%.
[0042] A C / C-SiC composite material prepared by a method for preparing a C / C-SiC composite material.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] The present invention utilizes graphene oxide grafted onto the surface of asphalt carbon fiber to form a transition layer, which can protect the carbon fiber from high-temperature corrosion of silicon and can also significantly improve the wettability with resin.
[0045] The preform structure adopted in the present invention is a three-dimensional orthogonal weaving of fibers, and the fiber volume fractions in each direction are close. Then, the expansion of silicon carbide and silicon can be limited by the negative expansion effect of carbon fibers, thereby achieving near-zero expansion of the composite material.
[0046] The composite material prepared by the present invention has the advantages of low density, near-zero thermal expansion coefficient in the plane and thickness direction, and excellent mechanical properties, and can meet the application requirements of optical-mechanical structural parts in a low-temperature space environment. DETAILED DESCRIPTION
[0047] The present invention is further described in detail below in conjunction with examples. It should be pointed out that the examples described below are intended to facilitate the understanding of the present invention and should not be regarded as specific limitations of the present invention.
[0048] The present invention provides a method for preparing a C / C-SiC composite material. Specifically, firstly, graphene oxide is grafted onto the surface of asphalt carbon fiber; the grafted graphene oxide forms a transition layer, which can protect the carbon fiber from high-temperature corrosion of silicon and significantly improve the wettability with resin. Then, the asphalt carbon fiber is woven into a three-dimensional quasi-isotropic asphalt carbon fiber preform; therefore, the fiber volume fractions in all directions of the asphalt carbon fiber preform are close; then, the thermosetting resin is evenly mixed with a curing agent and an organic solvent to prepare a resin slurry, and then the obtained asphalt carbon fiber preform is vacuum impregnated in the resin slurry, and then cured and cracked until the density of the asphalt carbon fiber preform reaches 1.30-1.50g / cm 3 , a porous C / C composite skeleton is obtained; finally, the porous C / C composite skeleton is subjected to reaction infiltration of silicon to carbonize the resin and react with silicon to generate SiC, thereby limiting the expansion of silicon carbide and silicon through the negative expansion effect of carbon fiber, and achieving near-zero expansion of the composite material. Specifically, the carbon fibers in the asphalt carbon fiber preform are perpendicular to each other in three directions, forming an orthogonal structure, and the edges of the asphalt carbon fiber preform form an interlocking structure; and the volume fraction of the asphalt carbon fiber in the X direction of the asphalt carbon fiber preform is 15-20 vol%; the volume fraction of the asphalt carbon fiber in the Y direction of the asphalt carbon fiber preform is 15-20 vol%; the volume fraction of the asphalt carbon fiber in the Z direction of the asphalt carbon fiber preform is 8-12 vol%. The C / C-SiC composite material prepared by the above method has a thermal expansion coefficient of about 0.03-0.46 ppm / K in the plane direction and about 0.18-0.69 ppm / K in the thickness direction within the temperature range of 25-200°C, both of which are close to 0. Therefore, its low thermal expansion coefficient characteristic can improve the adaptability of components prepared from C / C-SiC composite materials in an environment with drastic temperature changes in space.
[0049] Furthermore, the surface of the pitch carbon fiber can be modified by plasma first, and then graphene oxide can be grafted on the surface of the carbon fiber by silane coupling agent grafting method. Plasma treatment can modify the surface of the pitch carbon fiber, introduce a large number of polar groups on the fiber surface, and make the pitch carbon fiber better grafted with graphene oxide.
[0050] Graphene oxide can significantly improve the wettability with the resin precursor solution, significantly increase the bonding interface between carbon fiber and silicon carbide ceramic matrix, improve the interfacial bonding force between carbon fiber reinforcement and ceramic matrix, and ensure the effective transfer of load between ceramic matrix and fiber reinforcement. The silane coupling agent grafting method can build a "molecular bridge" between the interface of graphene oxide and asphalt carbon fiber, so that graphene oxide is grafted to the surface of carbon fiber to form a tight interface bond, increase the interfacial bonding strength, and prevent silicon-containing liquid from penetrating into the carbon fiber / graphene oxide interface during the subsequent precursor impregnation cracking and reaction infiltration process, effectively protecting the carbon fiber from high-temperature erosion by silicon.
[0051] Specifically, the plasma treatment method uses one or more of Ar, N2, and O2 as the ion; the plasma treatment method uses a discharge power of 200W-800W; and the plasma treatment method uses a treatment time of 10s-100s. Specifically, the alcohol dispersion of graphene oxide and the alcohol solution of silane coupling agent are mixed to obtain a coupling agent-modified graphene oxide dispersion, and then the plasma-treated pitch carbon fiber is immersed in the coupling agent-modified graphene oxide dispersion, and then taken out and dried to obtain carbon fiber with surface graphene oxide modified.
[0052] Specifically, in the alcohol dispersion of graphene oxide, the ratio of alcohol solvent to graphene oxide is 10mL:30-60mg; specifically, in the alcohol solution of silane coupling agent, the mass fraction of silane coupling agent is 2-5%;
[0053] Specifically, in the coupling agent-modified graphene oxide dispersion, the volume ratio of the graphene oxide alcohol dispersion to the silane coupling agent alcohol solution is 10:1-5.
[0054] Specifically, the silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane, and N-β (aminoethyl)-γ-aminopropyltriethoxysilane.
[0055] Further, the pitch carbon fiber preform is vacuum impregnated in resin slurry A, resin slurry B and resin slurry C with increasing amounts of residual carbon, followed by curing and cracking until the density of the pitch carbon fiber preform reaches 1.30-1.50 g / cm3, thereby obtaining a gradient porous C / C composite material skeleton;
[0056] The resin slurry A includes a thermosetting resin A;
[0057] The resin slurry B includes a thermosetting resin B;
[0058] The resin slurry C includes a thermosetting resin C;
[0059] The thermosetting resin A includes any one of epoxy resin, furan resin and trisphenol type phthalonitrile resin;
[0060] The thermosetting resin B includes any one of acetylene polyimide resin, bismaleimide resin and trisphenol type phthalonitrile resin;
[0061] The thermosetting resin C includes any one of polybenzoxazine resin, styrene-based polybenzoxazine resin and phenolic resin; the structure of the carbon skeleton impregnated with the thermosetting resin is controlled to be a gradient porous structure, the content of free silicon in the composite material after the reaction infiltration is reduced, and the obtained composite material has the advantages of low density, near-zero thermal expansion coefficient in the plane and thickness direction, and excellent mechanical properties, which can meet the application requirements of optical and mechanical structural parts in a low-temperature space environment. The present invention uses a multi-level residual carbon rate thermosetting resin for curing and cracking, and the escape of a large amount of gas in the process produces an obvious pore-forming effect, and the obtained carbon-based structure is a gradient porous structure. The structure of the carbon matrix impregnated and cracked by the multi-level residual carbon rate thermosetting resin precursor of the present invention is a gradient porous structure, which fills the large and small pores in the composite material, forms a gradient porous structure in the C / C composite material skeleton, and provides more, smaller and more evenly distributed reaction spaces for molten silicon in the subsequent reaction infiltration process, increases the specific surface area of the reaction, and effectively reduces the content of free silicon in the composite material. The mass percentage of free silicon in the composite material is reduced by 40-80%, and the strength is increased by 20-45%. Therefore, controlling the structure of the thermosetting resin impregnated cracked carbon skeleton to a gradient porous structure can reduce the content of free silicon in the composite material after reactive infiltration. Therefore, the resulting composite material has the advantages of low density, near-zero thermal expansion coefficient in the plane and thickness directions, and excellent mechanical properties, which can meet the application requirements of optomechanical structural parts in low-temperature space environments.
[0062] Specifically, the curing agent includes tetrahydrophthalic anhydride, xylene sulfonic acid, diethylenetriamine or urotropine; the organic solvent includes ethanol, dimethylformamide, acetone or xylene; in the resin slurry, the mass ratio of thermosetting resin, curing agent and organic solvent is 60-120:5-10:80-140.
[0063] Specifically, the vacuum degree of the vacuum impregnation is -0.1 to 0 MPa, and the time is 1 to 2 hours; the temperature of the curing is 100 to 150° C., and the time is 4 to 16 hours; the temperature of the pyrolysis is 800 to 1200° C., and the time is 1 to 5 hours.
[0064] Specifically, the vacuum degree of the reactive silicon infiltration is ≤1000Pa; the heating rate of the reactive silicon infiltration is 5 to 10°C / min; the insulation temperature of the reactive silicon infiltration is 1500 to 1800°C; the insulation time of the reactive silicon infiltration is 120 to 180min; the particle size of the silicon powder used for the reactive silicon infiltration is 30 to 50μm, and the mass fraction of silicon in the silicon powder is ≥98%.
[0065] Example 1
[0066] A method for preparing a near-zero expansion C / C-SiC composite material comprises the following steps:
[0067] (1) Surface modification of asphalt carbon fiber
[0068] A. Place the pitch carbon fiber on a plasma device, spray plasma onto the carbon fiber surface in an open environment, and make the carbon fiber move in the plasma atmosphere. The processing power is 100W, and the processing time is 60s to produce surface modification. The treated carbon fiber is vacuum dried at 60°C to constant weight to obtain plasma-treated carbon fiber.
[0069] B. Disperse 50 mg of graphene oxide in 10 mL of ethanol, add 2 mL of 5% silane coupling agent γ-aminopropyltriethoxysilane ethanol solution to obtain a silane coupling agent modified graphene oxide ethanol solution; immerse the plasma-treated carbon fiber in the silane coupling agent modified graphene oxide ethanol solution, take it out after 1 hour, and dry it at 60°C to obtain asphalt carbon fiber with surface graphene oxide modified.
[0070] (2) Preform preparation
[0071] The modified asphalt carbon fiber is three-dimensionally woven to obtain a three-dimensional quasi-isotropic asphalt carbon fiber preform with an asphalt carbon fiber volume fraction of 10 vol% in the Z direction and 15 vol% in the X and Y directions. The yarns in the three directions inside the woven structure are perpendicular to each other, forming an orthogonal structure and forming an interlocking structure at the edge of the preform.
[0072] (3) Preparation of C / C composite materials
[0073] A. First, epoxy resin, diethylenetriamine and xylene were weighed and mixed in a mass ratio of 120:10:80 to obtain resin slurry A. The asphalt carbon fiber preform was pressure-impregnated with slurry A and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. The preform was then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for 3 hours to obtain a porous C / C composite skeleton.
[0074] B. Then, bismaleimide resin, tetrahydrophthalic anhydride and dimethylformamide were weighed and mixed in a mass ratio of 80:10:120 to obtain resin slurry B. The porous C / C composite skeleton was pressure-impregnated with slurry B and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. The mixture was then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for pyrolysis for 3 hours to obtain a porous C / C composite skeleton.
[0075] C. Finally, phenolic resin, hexamethylenetetramine (urotropine) and ethanol were weighed and mixed in a mass ratio of 60:10:140 to obtain resin slurry C. The porous C / C composite skeleton was pressure-impregnated with slurry C and cured at 120°C for 4 hours. The impregnation pressure was 2 MPa for 2 hours. The temperature was then raised to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for pyrolysis for 3 hours to obtain a porous C / C composite skeleton. The density of the porous C / C composite skeleton reached 1.30 g / cm3 to obtain a C / C composite material.
[0076] (4) Ceramic densification
[0077] At 1650°C and vacuum conditions, Si powder (purity ≥98%, particle size 50 μm) is infiltrated into the C / C composite material obtained in step (3) for 120 min to obtain a C / C-SiC composite material with a density of 2.21 g / cm3, a thermal expansion coefficient in the plane direction of about 0.37 ppm / K (25-200°C), and a thermal expansion coefficient in the thickness direction of about 0.69 ppm / K (25-200°C).
[0078] Example 2
[0079] A method for preparing a near-zero expansion C / C-SiC composite material comprises the following steps:
[0080] (1) Surface modification of asphalt carbon fiber
[0081] A. Place the pitch carbon fiber on a plasma device, spray plasma onto the carbon fiber surface in an open environment, and make the carbon fiber move in the plasma atmosphere. The processing power is 100W, and the processing time is 60s to produce surface modification. The treated carbon fiber is vacuum dried at 60°C to constant weight to obtain plasma-treated carbon fiber.
[0082] B. Disperse 60 mg of graphene oxide in 10 mL of ethanol, add 2 mL of 5% silane coupling agent γ-aminopropyltriethoxysilane ethanol solution to obtain a silane coupling agent modified graphene oxide ethanol solution; immerse the plasma-treated carbon fiber in the silane coupling agent modified graphene oxide ethanol solution, take it out after 1 hour, and dry it at 60°C to obtain asphalt carbon fiber with surface graphene oxide modified.
[0083] (2) Preform preparation
[0084] The modified asphalt carbon fiber is three-dimensionally woven to obtain a three-dimensional quasi-isotropic asphalt carbon fiber preform with an asphalt carbon fiber volume fraction of 10 vol% in the Z direction and 15 vol% in the X and Y directions. The yarns in the three directions inside the woven structure are perpendicular to each other, forming an orthogonal structure and forming an interlocking structure at the edge of the preform.
[0085] (3) Preparation of C / C composite materials
[0086] A. First, furan resin, dimethylbenzenesulfonic acid and xylene are weighed and mixed in a mass ratio of 120:10:80 to obtain slurry A. The asphalt carbon fiber preform is pressure-impregnated with slurry A and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. The preform is then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for 3 hours to obtain a porous C / C composite skeleton.
[0087] B. Then, bismaleimide resin, tetrahydrophthalic anhydride and dimethylformamide were weighed and mixed in a mass ratio of 80:10:120 to obtain slurry B. The porous C / C composite skeleton was pressure-impregnated with slurry B and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. The mixture was then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for pyrolysis for 3 hours to obtain a porous C / C composite skeleton.
[0088] C. Finally, phenolic resin, hexamethylenetetramine (urotropine) and ethanol were weighed and mixed in a mass ratio of 60:10:140 to obtain slurry C. The porous C / C composite skeleton was pressure-impregnated with slurry C and cured at 120°C for 4 hours. The impregnation pressure was 2 MPa for 2 hours. The temperature was then raised to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for pyrolysis for 3 hours to obtain a porous C / C composite skeleton. The density of the porous C / C composite skeleton reached 1.40 g / cm3 to obtain a C / C composite material.
[0089] (4) Ceramic densification
[0090] At 1700°C and vacuum conditions, Si powder (purity ≥98%, particle size 50 μm) is infiltrated into the C / C composite material obtained in step (3) for 150 min to obtain a C / C-SiC composite material with a density of 2.31 g / cm3, a thermal expansion coefficient in the plane direction of about 0.46 ppm / K (25-200°C), and a thermal expansion coefficient in the thickness direction of about 0.59 ppm / K (25-200°C).
[0091] Example 3
[0092] A method for preparing a near-zero expansion C / C-SiC composite material comprises the following steps:
[0093] (1) Surface modification of asphalt carbon fiber
[0094] A. Place the pitch carbon fiber on a plasma device, spray plasma onto the carbon fiber surface in an open environment, and make the carbon fiber move in the plasma atmosphere. The processing power is 100W, and the processing time is 60s to produce surface modification. The treated carbon fiber is vacuum dried at 60°C to constant weight to obtain plasma-treated carbon fiber.
[0095] B. Disperse 60 mg of graphene oxide in 10 mL of ethanol, add 2 mL of 5% silane coupling agent γ-aminopropyltriethoxysilane ethanol solution to obtain a silane coupling agent modified graphene oxide ethanol solution; immerse the plasma-treated carbon fiber in the silane coupling agent modified graphene oxide ethanol solution, take it out after 1 hour, and dry it at 60°C to obtain asphalt carbon fiber with surface graphene oxide modified.
[0096] (2) Preform preparation
[0097] The modified asphalt carbon fiber is three-dimensionally woven to obtain a three-dimensional quasi-isotropic asphalt carbon fiber preform with an asphalt carbon fiber volume fraction of 10 vol% in the Z direction and 15 vol% in the X and Y directions. The yarns in the three directions inside the woven structure are perpendicular to each other, forming an orthogonal structure and forming an interlocking structure at the edge of the preform.
[0098] (3) Preparation of C / C composite materials
[0099] A. First, furan resin, dimethylbenzenesulfonic acid and xylene are weighed and mixed in a mass ratio of 120:10:80 to obtain slurry A. The asphalt carbon fiber preform is pressure-impregnated with slurry A and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. The preform is then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for 3 hours to obtain a porous C / C composite skeleton.
[0100] B. Then, triphenol-type phthalonitrile resin, tetrahydrophthalic anhydride and dimethylformamide were weighed and mixed in a mass ratio of 80:10:120 to obtain slurry B. The porous C / C composite skeleton was pressure-impregnated with slurry B and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. Then, the temperature was increased to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for cracking for 3 hours to obtain a porous C / C composite skeleton.
[0101] C. Finally, phenolic resin, hexamethylenetetramine (urotropine) and ethanol were weighed and mixed in a mass ratio of 60:10:140 to obtain slurry C. The porous C / C composite skeleton was pressure-impregnated with slurry C and cured at 120°C for 4 hours. The impregnation pressure was 2 MPa for 2 hours. The temperature was then raised to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for pyrolysis for 3 hours to obtain a porous C / C composite skeleton. The density of the porous C / C composite skeleton reached 1.50 g / cm3 to obtain a C / C composite material.
[0102] (4) Ceramic densification
[0103] At 1800°C and vacuum conditions, Si powder (purity ≥98%, particle size 50 μm) is infiltrated into the C / C composite material obtained in step (3) for 180 min to obtain a C / C-SiC composite material with a density of 2.26 g / cm3, a thermal expansion coefficient in the plane direction of about 0.23 ppm / K (25-200°C), and a thermal expansion coefficient in the thickness direction of about 0.18 ppm / K (25-200°C).
[0104] Comparative Example 1
[0105] A method for preparing a near-zero expansion C / C-SiC composite material comprises the following steps:
[0106] (1) Surface modification of asphalt carbon fiber
[0107] A. Place the pitch carbon fiber on a plasma device, spray plasma onto the carbon fiber surface in an open environment, and make the carbon fiber move in the plasma atmosphere. The processing power is 100W, and the processing time is 60s to produce surface modification. The treated carbon fiber is vacuum dried at 60°C to constant weight to obtain plasma-treated carbon fiber.
[0108] B. Disperse 60 mg of graphene oxide in 10 mL of ethanol, add 2 mL of 5% silane coupling agent γ-aminopropyltriethoxysilane ethanol solution to obtain a silane coupling agent modified graphene oxide ethanol solution; immerse the plasma-treated carbon fiber in the silane coupling agent modified graphene oxide ethanol solution, take it out after 1 hour, and dry it at 60°C to obtain asphalt carbon fiber with surface graphene oxide modified.
[0109] (2) Preform preparation
[0110] The modified asphalt carbon fiber is three-dimensionally woven to obtain a three-dimensional quasi-isotropic asphalt carbon fiber preform with an asphalt carbon fiber volume fraction of 10 vol% in the Z direction and 15 vol% in the X and Y directions. The yarns in the three directions inside the woven structure are perpendicular to each other, forming an orthogonal structure and forming an interlocking structure at the edge of the preform.
[0111] (3) Preparation of C / C composite materials
[0112] Firstly, furan resin, dimethylbenzenesulfonic acid and xylene were weighed and mixed in a mass ratio of 120:10:80 to obtain slurry A. The asphalt carbon fiber preform was pressure impregnated with slurry A and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. Then the preform was heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for 3 hours until the density of the porous C / C composite skeleton reached 1.50 g / cm3 to obtain a C / C composite material.
[0113] (4) Ceramic densification
[0114] At 1800°C and under vacuum conditions, Si powder (purity ≥98%, particle size 50 μm) is infiltrated into the C / C composite material obtained in step (3) for 180 min to obtain a C / C-SiC composite material with a density of 1.95 g / cm3, a thermal expansion coefficient in the plane direction of about -0.64 ppm / K (25-200°C), and a thermal expansion coefficient in the thickness direction of about 1.44 ppm / K (25-200°C).
[0115] Comparative Example 2
[0116] A method for preparing a near-zero expansion C / C-SiC composite material comprises the following steps:
[0117] (1) Surface modification of asphalt carbon fiber
[0118] A. Place the pitch carbon fiber on a plasma device, spray plasma onto the carbon fiber surface in an open environment, and make the carbon fiber move in the plasma atmosphere. The processing power is 100W, and the processing time is 60s to produce surface modification. The treated carbon fiber is vacuum dried at 60°C to constant weight to obtain plasma-treated carbon fiber.
[0119] B. Disperse 60 mg of graphene oxide in 10 mL of ethanol, add 2 mL of 5% silane coupling agent γ-aminopropyltriethoxysilane ethanol solution to obtain a silane coupling agent modified graphene oxide ethanol solution; immerse the plasma-treated carbon fiber in the silane coupling agent modified graphene oxide ethanol solution, take it out after 1 hour, and dry it at 60°C to obtain asphalt carbon fiber with surface graphene oxide modified.
[0120] (2) Preform preparation
[0121] The modified asphalt carbon fiber is two-dimensionally woven to obtain a two-dimensional asphalt carbon fiber preform with an asphalt carbon fiber volume fraction of 20 vol% in the X and Y directions, and the yarns in the two directions inside the woven structure are perpendicular to each other.
[0122] (3) Preparation of C / C composite materials
[0123] A. First, furan resin, dimethylbenzenesulfonic acid and xylene are weighed and mixed in a mass ratio of 120:10:80 to obtain slurry A. The asphalt carbon fiber preform is pressure-impregnated with slurry A and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. The preform is then heated to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for 3 hours to obtain a porous C / C composite skeleton.
[0124] B. Then, triphenol-type phthalonitrile resin, tetrahydrophthalic anhydride and dimethylformamide were weighed and mixed in a mass ratio of 80:10:120 to obtain slurry B. The porous C / C composite skeleton was pressure-impregnated with slurry B and cured at 120°C for 4 hours with an impregnation pressure of 2 MPa for 2 hours. Then, the temperature was increased to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for cracking for 3 hours to obtain a porous C / C composite skeleton.
[0125] C. Finally, phenolic resin, hexamethylenetetramine (urotropine) and ethanol were weighed and mixed in a mass ratio of 60:10:140 to obtain slurry C. The porous C / C composite skeleton was pressure-impregnated with slurry C and cured at 120°C for 4 hours. The impregnation pressure was 2 MPa for 2 hours. The temperature was then raised to 800°C in a nitrogen atmosphere at a heating rate of 5°C / min for pyrolysis for 3 hours to obtain a porous C / C composite skeleton. The density of the porous C / C composite skeleton reached 1.50 g / cm3 to obtain a C / C composite material.
[0126] (4) Ceramic densification
[0127] At 1800°C and vacuum conditions, Si powder (purity ≥98%, particle size 50 μm) is infiltrated into the C / C composite material obtained in step (3) for 180 min to obtain a C / C-SiC composite material with a density of 2.35 g / cm3, a thermal expansion coefficient in the plane direction of about 1.13 ppm / K (25-200°C), and a thermal expansion coefficient in the thickness direction of about 2.18 ppm / K (25-200°C).
[0128] The composite material performance results are shown in Table 1
[0129]
[0130]
Claims
1. A method for preparing a C / C-SiC composite material, characterized in that: The steps include: S1 grafted graphene oxide onto the surface of asphalt carbon fiber; S2 weaves the pitch carbon fiber obtained in S1 into a three-dimensional quasi-isotropic pitch carbon fiber preform; S3 mixes the thermosetting resin, the curing agent and the organic solvent evenly to obtain a resin slurry, and then vacuum impregnates the asphalt carbon fiber preform obtained in S2 into the resin slurry, and then cures and cracks the asphalt carbon fiber preform until the density of the asphalt carbon fiber preform reaches 1.30-1.50g / cm 3 , a porous C / C composite skeleton is prepared; S4: reacting and infiltrating silicon into the gradient porous C / C composite material skeleton obtained in S3 to obtain the C / C-SiC composite material; the carbon fibers in the asphalt carbon fiber preform are perpendicular to each other in three directions to form an orthogonal structure, and the edges of the asphalt carbon fiber preform form an interlocking structure; In the X direction of the pitch carbon fiber preform, the volume fraction of the pitch carbon fiber is 15-20 vol%; In the Y direction of the pitch carbon fiber preform, the volume fraction of the pitch carbon fiber is 15-20 vol%; In the Z direction of the pitch carbon fiber preform, the volume fraction of the pitch carbon fiber is 8-12 vol%; The C / C-SiC composite material has a thermal expansion coefficient of about 0.03-0.46 ppm / K in the plane direction and a thermal expansion coefficient of about 0.18-0.69 ppm / K in the thickness direction.
2. The method for preparing the C / C SiC composite material according to claim 1, characterized in that: The S1 is to use plasma to modify the surface of the asphalt carbon fiber, and then use a silane coupling agent grafting method to graft graphene oxide on the surface of the carbon fiber.
3. The method for preparing the C / C-SiC composite material according to claim 2, characterized in that: The ions used in the plasma treatment method are one or more of Ar, N2, and O2; The discharge power used in the plasma treatment method is 200W-800W; The plasma treatment method uses a treatment time of 10s-100s.
4. The method for preparing the C / C-SiC composite material according to claim 2, characterized in that: The S1 comprises the steps of mixing an alcohol dispersion of graphene oxide and an alcohol solution of a silane coupling agent to obtain a coupling agent-modified graphene oxide dispersion, and then immersing the plasma-treated pitch carbon fiber in the coupling agent-modified graphene oxide dispersion, and then taking out and drying.
5. The method for preparing the near-zero expansion C / C-SiC composite material according to claim 4, characterized in that: In the alcohol dispersion of graphene oxide, the ratio of alcohol solvent to graphene oxide is 10 mL: 30-60 mg; In the alcohol solution of the silane coupling agent, the mass fraction of the silane coupling agent is 2-5%; In the coupling agent-modified graphene oxide dispersion, the volume ratio of the graphene oxide alcohol dispersion to the silane coupling agent alcohol solution is 10:1-5.
6. The method for preparing a near-zero expansion C / C-SiC composite material according to claim 4, characterized in that: The silane coupling agent is at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-β (aminoethyl)-γ-aminopropyltrimethoxysilane and N-β (aminoethyl)-γ-aminopropyltriethoxysilane.
7. The method for preparing the C / C-SiC composite material according to claim 1, characterized in that: The method comprises vacuum impregnating the asphalt carbon fiber preform obtained in S2 in resin slurries A, B and C with increasing amounts of residual carbon, followed by curing and cracking until the density of the asphalt carbon fiber preform reaches 1.30-1.50 g / cm 3 , the step of preparing a gradient porous C / C composite skeleton; The resin slurry A includes a thermosetting resin A; The resin slurry B includes a thermosetting resin B; The resin slurry C includes a thermosetting resin C; The thermosetting resin A includes any one of epoxy resin, furan resin and trisphenol type phthalonitrile resin; The thermosetting resin B includes any one of acetylene polyimide resin, bismaleimide resin and trisphenol type phthalonitrile resin; The thermosetting resin C includes any one of polybenzoxazine resin, styrene-based polybenzoxazine resin and phenolic resin; the curing agent includes tetrahydrophthalic anhydride, xylene sulfonic acid, diethylenetriamine or hexamethylenetetramine; The organic solvent includes ethanol, dimethylformamide, acetone or xylene; In the resin slurry, the mass ratio of the thermosetting resin, the curing agent and the organic solvent is 60-120:5-10:80-140.
8. The method for preparing the C / C-SiC composite material according to claim 1, characterized in that: The vacuum degree of the vacuum impregnation is -0.1-0MPa, and the time is 1-2h; The curing temperature is 100-150°C and the curing time is 4-16h; The cracking temperature is 800-1200° C. and the time is 1-5 hours.
9. The method for preparing the C / C-SiC composite material according to claim 1, characterized in that: The vacuum degree of the reactive silicon infiltration is ≤1000Pa; The heating rate of the reactive infiltration silicon is 5-10°C / min; The insulation temperature of the reactive infiltration silicon is 1500-1800°C; The holding time of the reactive silicon infiltration is 120-180 minutes; The particle size of the silicon powder used for the reactive infiltration of silicon carbide is 30-50 μm, and the mass fraction of silicon in the silicon powder is ≥98%.
10. The C / C-SiC composite material prepared by the method for preparing a C / C-SiC composite material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of C / C-SiC (carbon fiber reinforced carbon-silicon carbide) composite with low CTE (coefficient of thermal expansion)
CN105060913A
High-compactness silicon carbide ceramic-based composite material and preparation method thereof
CN106588060A
Preparation method of graphene oxide modified carbon fiber reinforced silicon carbide ceramic matrix composite
CN110078515A
Near-zero-expansion carbon fiber reinforced multi-element multi-layer matrix composite material as well as preparation method and application thereof
CN117185818A
High-thermal-conductivity low-expansion carbon ceramic material and preparation method thereof
CN117923931A